The fruits of empirical linguistics - Featherston, Sam 1953-; Winkler, Susanne 1960- (Studies in generative grammar, 2009)
The second volume of the two-volume set The Fruits of Empirical Linguistics focuses on the linguistic outcomes of empirical linguistics. The contributions present some of the insights that linguists can gain by applying the new methods: progress within language study is accelerated by the new evidence since language systems are more precisely captured. Readers will enjoy the fresh perspective on linguistic questions made possible by the evidence-based approach